Classification of Fire Risk Scenarios in the State of Pará Using Multicriteria Analysis - Sousa, Enéas Monteiro; Negreiros, Waldemiro José Assis Gomes; Kuribayashi, Hugo Pereira; Silva, Jeova Rafael Rodrigues Da; DeSouza, G. N.; Seruffo, Marcos César da Rocha (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2026: Anais do XVII Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos NaturaisDO - 10.5753/wcama.2026.23625, 2026)
Wildfires in the Brazilian Amazon are shaped by climatic and anthropogenic factors and require decision-support methods. This study proposes a multicriteria model to classify wildfire risk scenarios across municipalities in Pará. Environmental indicators from remote sensing and public databases are integrated with weights derived from the Analytic Hierarchy Process (AHP) and ELECTRE Tri-B classification. Municipalities are assigned to low, moderate, high, and critical risk categories. The results support the identification of priority areas for environmental monitoring and territorial management.